Total hip arthroplasty performed by direct anterior approach – Does experience influence the learning curve? - Foissey Constant; Fauvernier Mathieu; Fary Cam; Servien Elvire; Lustig Sébastien; Batailler Cécile (SICOT-J, 2020)
Introduction: Proficiency in the direct anterior approach (DAA) as with many surgical techniques is considered to be challenging. Added to this is the controversy of the benefits of DAA compared to other total hip arthroplasty (THA) approaches. Our study aims to assess the influence of experience on learning curve and clinical results when transitioning from THA via posterior approach in a lateral position to DAA in a supine position. Methods: A consecutive retrospective series of 525 total hip arthroplasty of one senior and six junior surgeons was retrospectively analysed from May 2013 to December 2017. Clinical results were analysed and compared between the two groups and represented as a learning curve. Mean follow up was 36.2 months ± 11.8. Results: This study found a significant difference in complications between the senior and junior surgeons for operating time, infection rate, and lateral femoral cutaneous nerve (LFCN) neuropraxia. A trainee’s learning curve was an average of 10 DAA procedures before matching the senior surgeon. Of note, the early complications correlated with intraoperative fractures increased with experience in both groups. Operating time for the senior equalised after 70 cases. Dislocation rate and limb length discrepancy were excellent and did not show a learning curve between the two groups. Conclusion: DAA is a safe approach to implant a THA. There is a learning curve and initial supervision is recommended for both seniors and trainees. Level of evidence: Retrospective, consecutive case series; level IV.